Uma criança como outra qualquer? A criança transexual em diálogo com a teoria Queer - Silva, Bianca Neves Borges da (2019)
This paper focuses on discussions about children who don’t identify themselves and express a disagreement with following socially pre-established gender norms and standards. Such standards are strongly established within church, family, and school institutions and are rooted in a heteronormative and binary logic that not only nullifies children's various ways of expressing and living, but violates their basic rights as human beings. There is also another side, which is that these same children are being portrayed in the media in a way perhaps as violent as those treated in other institutions. They are being classified, medicalized, analyzed by experts as deviant and abnormal. To fulfill the objective of analyzing how this transgender child is invented and presented to society by the Brazilian television media, which today has consolidated itself as one of the largest mass media and information, we conducted: (a) a bibliographic research with the survey of all news found on the google.com search engine from 2010 to 2018 dealing with the theme of transgender children; (b) theoretical survey with academic publications on the same theme and at the same time frame in the googleschoolar.com search engine, in order to understand what the academic field has debated about these children; (c) analysis of the video report about “Coy” produced by the program “Fantástico”. The theoretical analysis of this work is based on Queer studies and reflections that fit the non-identity paradigm, problematizing the way in which identities are constructed, whatever, how many and how they are. With this research we try to contribute to the debate by revealing the violence experienced by children who are neglected in their singularities, do not have their wishes respected and are ridiculed when they try to live their desires in some way, and at the same time, the process of plaster that occurs when they put them in a new category that is equally identity.